2022
DOI: 10.1371/journal.ppat.1010305
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-1-driven neutrophil pyroptosis and its role in host susceptibility to Pseudomonas aeruginosa

Abstract: Multiple regulated neutrophil cell death programs contribute to host defense against infections. However, despite expressing all necessary inflammasome components, neutrophils are thought to be generally defective in Caspase-1-dependent pyroptosis. By screening different bacterial species, we found that several Pseudomonas aeruginosa (P. aeruginosa) strains trigger Caspase-1-dependent pyroptosis in human and murine neutrophils. Notably, deletion of Exotoxins U or S in P. aeruginosa enhanced neutrophil death to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
70
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(82 citation statements)
references
References 77 publications
9
70
1
Order By: Relevance
“…Finally, Oh et al 78 described the ability of Yptb‐ΔyopM infection to facilitate NETosis downstream of active pyrin inflammasome assembly and accumulation of pro‐pyroptotic N‐GSDMD pores in the plasma membrane. Similar to the findings of Santoni et al 79 with P. aeruginosa ‐infected neutrophils, PAD4‐mediated H3 histone citrullination was triggered by Ca 2+ influx through the plasma membrane N‐GSDMD pores that accumulated in Yptb‐ΔyopM infected neutrophils. Dissimilar from the observations of Santoni et al 79 the PAD4‐mediated H3 histone citrullination induced in Yptb‐ΔyopM infected cells correlated with expulsion of the decondensed chromatin into the extracellular space as NETs surrounding the lysed neutrophils.…”
Section: Neutrophil Inflammasome Signaling Pathways That Facilitate R...supporting
confidence: 85%
See 1 more Smart Citation
“…Finally, Oh et al 78 described the ability of Yptb‐ΔyopM infection to facilitate NETosis downstream of active pyrin inflammasome assembly and accumulation of pro‐pyroptotic N‐GSDMD pores in the plasma membrane. Similar to the findings of Santoni et al 79 with P. aeruginosa ‐infected neutrophils, PAD4‐mediated H3 histone citrullination was triggered by Ca 2+ influx through the plasma membrane N‐GSDMD pores that accumulated in Yptb‐ΔyopM infected neutrophils. Dissimilar from the observations of Santoni et al 79 the PAD4‐mediated H3 histone citrullination induced in Yptb‐ΔyopM infected cells correlated with expulsion of the decondensed chromatin into the extracellular space as NETs surrounding the lysed neutrophils.…”
Section: Neutrophil Inflammasome Signaling Pathways That Facilitate R...supporting
confidence: 85%
“…Recent functional studies have demonstrated that human and murine neutrophils express high levels of GSDMD 54,56,75,78,79,99–106 and GSDME 78,102 protein; analyses of the possible expression of the other GSDM proteins in neutrophils have not been reported. Although comprehensive transcriptomic profiling of GSDM family expression in neutrophils has not been reported, our RNA‐Seq analysis of FACS isolated (>99%) murine neutrophil populations revealed high gene expression of GSDME and GSDMD, but no other murine GSDM family members (E. Pearlman and G.R.…”
Section: Inflammasomes and Gasdermins As Critical Regulators Of Pyrop...mentioning
confidence: 99%
“…Although major research studies unveiled that upon acute infection, P. aeruginosa T3SS allows both activation of the NLRC4 and NLRP3 inflammasomes in rodent as well as in human macrophage and neutrophil models (Sutterwala et al, 2007; Faure et al, 2014; Franchi et al, 2007; Miao et al, 2008; Deng et al, 2015; Balakrishnan et al, 2018; Santoni et al, 2022a; Ryu et al, 2016), chronic infections mediated by this pathogen is associated with a downregulation of T3SS in favor a biofilm phenotype, where EXOA is strongly produced and released. To this regard, our observation that EXOA-driven ribotoxic stress contributes to exacerbated tissue damage and inflammation strongly correlate with earlier studies which showed that EXOA-deficient bacteria triggered lower tissue damages during infections of human and mice (Michalska and Wolf, 2015; Pillar and Hobden, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Specific deletion of xcpQ (T2SS) and toxA (EXOA) genes was achieved as described previously in (Santoni et al, 2022b). Briefly, pEXG2 suicide vector containing 700-bp sequences of the flanking regions of the selected gene was directly inserted into competent SM10λpir (Mix&Go competent cells, Zymo Research Corporation) and subsequently selected on LB-Agar supplemented with 50 μg/mL kanamycin /15 μg/mL gentamicin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation